Rapid Pyrolysis of Raw and Pretreated Biomass under Conditions Pertinent to Pulverized Fuel Applications - Shen, Qiqing (Curtin University, 2021)
This Ph.D. study investigates the rapid pyrolysis of biomass at high temperatures and the properties of derived char samples under various conditions. A novel drop-tube furnace was used to experimentally determine the accurate char yields after rapid pyrolysis at 1300°C, which is realized for the first time. Based on true char yield, the evolution of char properties was revealed, and the retention of inorganic species, the transformation of particle shape during rapid pyrolysis were quantified.